ASSOCIATIONS OF EARLY COMPLEMENTARY FEEDING, MATERNAL HYGIENE, AND HOME SANITATION WITH DIARRHEA AMONG INFANTS 0-6 MONTHS - Dewinta, Mustika Cahya Nirmala; Meldi, Putri Apriliani; Ayu, Suci Musvita; Jatmika, Septian Emma Dwi; Kodriati, Nurul; Sukarelawan, Moh. Irma (JURNAL KESEHATAN REPRODUKSI, 2024)
Background: Diarrhea in infants aged 0-6 months is one of the leading causes of morbidity and mortality in developing countries. Objective: This study aims to analyze the relationship between early complementary feeding, personal hygiene habits, sanitation system conditions, availability of waste/trash bins, and household sewage systems on the incidence of diarrhea in infants. Method: This analytical observational study used a cross-sectional design conducted at the Borong Health Centre, East Manggarai Regency, NTT. A total of 51 mothers of infants aged 0–6 months were selected using total population sampling. Data were collected through interviews and observations using a questionnaire and then analyzed with bivariate and multivariate tests. Results: Bivariate analysis showed significant associations between ECF, availability of proper trash bins, and household wastewater disposal systems with diarrhea (p < 0.05). ECF increased the risk of diarrhea by 3.95 times, while poor trash bin availability increased the risk by 4.00 times. Multivariate analysis showed risk trends but no statistical significance after adjusting for confounders. Conclusion: Early complementary feeding, availability of waste bins, and household sanitation systems play important roles in increasing the risk of diarrhea among infants aged 0-6 months.